2015
DOI: 10.5897/ijps2015.4406
|View full text |Cite
|
Sign up to set email alerts
|

A study of structural, optical and dielectric properties of Eu2O3 doped borate glass

Abstract: Recent technological applications have generated more interest in the studies of different types of glasses. The wide applications of glasses take place due to their interesting properties such as low thermal expansion, high softening temperature, high resistance to chemical attack, high refractive index with low dispersion and mechanical strength. Eu 2 O 3 doped borate glasses were successfully synthesized by melt quenching method. The X-ray diffraction (XRD) spectra revealed that these glasses had amorphous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…However beyond 1 mol %, the emission intensity 108 Solid State Science and Technology XXIX decreases as a result of concentration quenching on the luminescence. Generally, it is found that an excessive doping of emission spectrum ion in inorganic materials could significantly lower the emission intensity [11]. This result is consistent with Bandi et al, (2012) who claimed that this phenomenon is known as the concentration quenching [12].…”
Section: Resultssupporting
confidence: 84%
“…However beyond 1 mol %, the emission intensity 108 Solid State Science and Technology XXIX decreases as a result of concentration quenching on the luminescence. Generally, it is found that an excessive doping of emission spectrum ion in inorganic materials could significantly lower the emission intensity [11]. This result is consistent with Bandi et al, (2012) who claimed that this phenomenon is known as the concentration quenching [12].…”
Section: Resultssupporting
confidence: 84%